Vibrational and rotational spectroscopy of (CD3OD)-C-13 - Viscovini, R. C.; Cruz, F. C.; Moraes, João Carlos Silos [UNESP]; Scalabrin, A.; Pereira, D. (Kluwer Academic/plenum Publ, 1999)
We have used Fourier Transform spectral data on the C-O stretching mode of (CD3OD)-C-13 in order to perform a vibro-rotational analysis for this molecule. We have estimated a few molecular parameters of the ground and C-O stretching vibrational modes. Based on these parameters, and by using the Kwan-Dennison model, we propose assignments for a number of far-infrared laser transitions of (CD3OD)-C-13.
Keywords: lasers; assignments; (CD3OD)-C-13